1992
DOI: 10.1089/aid.1992.8.1619
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Envelope Region of the Highly Divergent HIV-2ALTIsolate Extends the Known Range of Variability Within the Primate Immunodeficiency Viruses

Abstract: HIV-2ALT is a highly divergent HIV-2-related isolate that is genetically equidistant to the prototypic HIV-2 strains, defined by HIV-2ROD, and to the simian immunodeficiency viruses SIVmac and SIVsm. We have now cloned and sequenced the envelope region of HIV-2ALT, thus completing the analysis of the whole viral genome. The sequences of env and nef and of the second exons of tat and rev were compared with those of the other viruses of the HIV-2/SIVsm/SIVmac group. Despite of the high degree of variation of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…1B) of the self-computation of the concatemerized HIV2s (designated "allhiv2" in the figures) is similar to that for HIVls (Fig, 1A). Of particular interest were the HIV2D2O5 and HIV2uc 1 strains previously described as being divergent (Gao et al 1992;Kreutz et al 1992), a result which was corroborated on lines L1 and L2 of Fig. 1B, respectively.…”
Section: Self-comparison Of the Viral Glvupssupporting
confidence: 75%
“…1B) of the self-computation of the concatemerized HIV2s (designated "allhiv2" in the figures) is similar to that for HIVls (Fig, 1A). Of particular interest were the HIV2D2O5 and HIV2uc 1 strains previously described as being divergent (Gao et al 1992;Kreutz et al 1992), a result which was corroborated on lines L1 and L2 of Fig. 1B, respectively.…”
Section: Self-comparison Of the Viral Glvupssupporting
confidence: 75%
“…Identical residues were replaced by dots and gaps introduced for optimal alignment are shown as horizontal lines. Verification of our earlier described sequence (Kreutz et al, 1992) of the nef open reading frame of HIV-2 D205 revealed some discrepancies in the amino-terminal region of the protein. The corrected sequence is used here.…”
Section: The Nef Proteins Of Divergent Hiv-strains Differ In Their Bimentioning
confidence: 78%
“…Specimen sequences from HIV-1 subtypes (A, B and D), HIV-2 subtypes (a and b) and SIV from chimpanzee, African green and macaque/sooty mangabey monkeys were analysed, as described in Methods, to determine virus groupings and allow confirmation of the direction of evolution. The tree was based on 1842 nucleotides for each of 25 sequences and gave branching patterns comparable to those generated by the neighbour-joining method for gag/pol (Myers et al, 1992) and env (Kreutz et al, 1992) genes. In agreement with the previous publications, infection of man with HIV-2a and b subtypes appears to have occurred as independent events.…”
Section: ===-Eq---===--e-d---n===---h--i-===-nm---mentioning
confidence: 99%
“…Immunologically (Robert-Guroff et al, 1992) and genetically ) HIV-2 is more closely related to certain of the simian immunodeficiency viruses, SIVs~ and SIVMAe which cause immunodeficiency in macaque and sooty mangabey monkeys, than to HIV-I. The HIV-2b subtype currently contains three viruses, HIV-2D205/ALr (Kreutz et al, 1992), HIV-2~n 2 (Kawamura et al, 1992) and HIV-2vc 1 (Barnett et al, 1993) and is phylogenetically closer to HIV-1 and SIVAQ M than to the HIV-2a subtype and the SIVsMmA c group. Viruses indistinguishable from SIVsMmA c have been identified in asymptomatic HIV-2 seropositive Liberian rural workers (Gao et al, 1992) and sequencing studies of env and gag genes have led to the proposal of at least five HIV-2 subtypes (A-E, Sharp et al, 1994).…”
Section: Introductionmentioning
confidence: 99%